Simultaneous Interrogation of Cancer Omics to Identify Subtypes With Significant Clinical Differences - Xu, Aodan; Chen, Jiazhou; Peng, Hong; Han, GuoQiang; Cai, Hongmin (Frontiers in Genetics, 2019)
Recent advances in high-throughput sequencing have accelerated the accumulation of omics data on the same tumor tissue from multiple sources. Intensive study of multi-omics integration on tumor samples can stimulate progress in precision medicine and is promising in detecting potential biomarkers. However, current methods are restricted owing to highly unbalanced dimensions of omics data or difﬁculty in assigning weights between different data sources. Therefore, the appropriate approximation and constraints of integrated targets remain a major challenge. In this paper, we proposed an omics data integration method, named high-order path elucidated similarity (HOPES). HOPES fuses the similarities derived from various omics data sources to solve the dimensional discrepancy, and progressively elucidate the similarities from each type of omics data into an integrated similarity with various high-order connected paths. The fused similarity matrix gives global insight into patients’ correlation and efﬁciently distinguishes subgroups. We tested the performance of HOPES on both a simulated dataset and several empirical tumor datasets. The test datasets contain three omics types including gene expression, DNA methylation, and microRNA data for ﬁve different TCGA cancer projects. Our method was ﬁrst shown to achieve superior accuracy and high robustness compared with several benchmark methods on simulated data. Further experiments on ﬁve cancer datasets demonstrated that HOPES achieved superior performances in cancer classiﬁcation. The stratiﬁed subgroups were shown to have statistically signiﬁcant differences in survival. We further located and identiﬁed the key genes, methylation sites, and microRNAs within each subgroup. They were shown to achieve high potential prognostic value and were enriched in many cancer-related biological processes or pathways.